Prevalence and determinants of self‐reported anxiety and stress among women with abortion‐related complications admitted to health facilities in Eastern and Southern Africa: A cross‐sectional survey. (11th January 2022) - Pershad, Jyoti; Mugerwa, Kidza Yvonne; Filippi, Veronique; Mehrtash, Hedieh; Adu‐Bonsaffoh, Kwame; Bello, Folasade Adenike; Compaoré, Rachidatou; Gadama, Luis; Govule, Philip; Qureshi, Zahida; Tunçalp, Ӧzge; Calvert, Clara
Abstract: Objective: To estimate the prevalence of women who were admitted to health facilities with abortion‐related complications who reported feeling anxious/stressed during their stay, and to identify sociodemographic, facility, and abortion‐related characteristics associated with self‐reported experience of anxiety/stress. Methods: We used data from four countries in Eastern and Southern Africa (Kenya, Malawi, Mozambique, and Uganda) collected from 2017–2018 as part of the World Health Organization (WHO) Multi‐Country Survey on Abortion‐related morbidity (MCS‐A). Information was extracted from women's medical records and their participation in audio computer‐assisted self‐interviews (ACASI). Based on a question in the ACASI, "Did you encounter any anxiety or stress during your hospital stay?", the percentage of women who self‐reported feeling anxious/stressed during their facility stay was calculated. Generalized estimating equations were used to identify the determinants of anxiety/stress following a hierarchical approach whereby potential determinants were grouped from most distal to most proximal and analyzed accordingly. Results: There were 1254 women with abortion‐related complications included in the analysis, of which 56.5% self‐reported that they felt anxious/stressed during their facility stay. We found evidence that lower socioeconomic status, lower levels of education, no previous childbirth, no previous abortion, higher gestational age at abortion, and use of unsafe methods of abortion were independent determinants of self‐reporting anxiety/stress. Conclusions: Action should be taken to reduce experience of anxiety/stress among women attending facilities for postabortion complications, including reducing the number of women experiencing abortion‐related complications by improving access to safe abortion. This issue warrants further study using more comprehensive and validated tools to understand the levels and drivers of anxiety/stress self‐reported by women attending facilities with abortion‐related complications. Synopsis: We found that 56.5% of women attending facilities with abortion‐related complications self‐reported experiencing anxiety/stress during their facility stay. Further research should be conducted to investigate this with validated tools.